Effect of Temperature, Concentration, and Type of Plasticizer on Edible Pectin Film Characteristics of Mango Peel (Mangifera indica L.) - Eka Wahyu Asriyanti; Muna Munisah; Erlando Rizki Dewanto; Muhammad Mujiburohman (Universitas Ahmad Dahlan, 2022)
Plastic is a polymer product that is widely used by the community and is generally non-degradable. Its high usage makes plastic a source of waste that is difficult to decompose. It is important to transform the use of degradable materials as packaging by the community in an effort to overcome plastic waste. The edible film is an environmentally friendly packaging medium, which is generally synthesized from a mixture of pectin, plasticizer, and tapioca starch by heating and stirring. This study aims to study the effect of mixing temperature, pectin concentration, and type of plasticizer on the characteristics of the edible film. The temperature was varied at 70 oC, 80 oC, and 90 oC, with variations in pectin concentrations of 1%, 2%, and 3%. The types of plasticizers used were glycerol, sorbitol, and polyethylene glycol (PEG 400). The characteristics of the edible film were tested from thickness, tensile strength, elongation, and solubility. In the range of variables studied, the optimum conditions for producing the best edible film characteristics were 70 oC, 3% pectin, and the plasticizer of glycerol, giving solubility of 0.670 g water/g edible film, the thickness of 0.392 mm, the tensile strength of 3.200 MPa, and elongation of 0.134.